Evidance Based Practice Penerapan Kompres Air Hangat untuk Menurunkan Demam dengan Diagnosa Demam Berdarah Dengue - Manampiring, Dio Juventa; Kairupan, Michelle Jessica; Lontoh, Esther (JURNAL ILMIAH KESEHATAN MANADO, 2025)
The number of dengue fever (DHF) cases in North Sulawesi in 2021 was recorded at 1,196, with 32 deaths. Meanwhile, from January to June 2023, there were 1,120 cases of DHF in North Sulawesi. In Manado City, there were 230 cases of DHF in 2023. The purpose of this case study is to analyze the evidence-based practice of warm water compresses on An.E.M. to reduce fever. implementing interventions according to the EBN journal "nursing care with the application of evidence-based warm water compresses to reduce fever. The final evaluation results showed that An. E. M's body temperature on July 24, 2024 was known before being given warm water compress therapy, the client's body temperature was 38.00C, and after the intervention, the client's body temperature was 37.70C. On July 25, 2024, it was known before being given warm water compress therapy, the client's body temperature was 37.70C, and after the intervention, the client's body temperature was 36.20C. On July 26, 2024, it was known before being given warm water compress therapy, the client's body temperature was 36.80C, and after the intervention, the client's body temperature was 36.00C. These results indicate that the intervention that had been carried out for 3 days had a change or decrease in the client's body temperature after the application of warm water compress therapy.